2020
DOI: 10.1080/10717544.2020.1833382
|View full text |Cite
|
Sign up to set email alerts
|

A sustained dual drug delivery system for proliferative vitreoretinopathy

Abstract: Proliferative vitreoretinopathy (PVR) is a significant threat for vision recovery from retinal detachment or ocular trauma. Currently, no approved pharmacological intervention to prevent PVR. Daunorubicin (DNR) and dexamethasone (DEX) were sequentially loaded into oxidized porous silicon (pSiO 2) particles by covalent conjugation. The DNR þ DEX-loaded particles, and control particles loaded with DNR only and DEX only were incubated with RPE-populated collagen for daily gel surface quantitation. Toxicity was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Müller cell gliosis also plays an important role in the development of PVR [15,[44][45] . Xiao et al [13] reported that Müller cells were activated on day 3 after retinal detachment induced by infusing sodium hyaluronate into the subretinal space through a tiny retinotomy. However, in the case of traumatic PVR, the status and extent of Müller cell reaction have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Müller cell gliosis also plays an important role in the development of PVR [15,[44][45] . Xiao et al [13] reported that Müller cells were activated on day 3 after retinal detachment induced by infusing sodium hyaluronate into the subretinal space through a tiny retinotomy. However, in the case of traumatic PVR, the status and extent of Müller cell reaction have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is needed for further research on the progression of traumatic PVR. Following ocular trauma, gliotic changes in the retina have an essential role in PVR pathologic process associated with retinal stiffness and shortening [10][11][12][13] ; and the primary participating cellular components are Müller glial cells [14][15] . Glial fibrillary acid protein (GFAP) is considered a sensitive biomarker for reactive Müller gliosis and correlates positively with PVR severity [16] .…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of clinical application is the creation of nanocarriers to deliver CRISPR-Cas9 into specific cancer cells [ 90 ]. Polymer nanoparticles [ 88 , 91 , 92 ], lipid nanoparticles [ 93 , 94 , 95 ], and porous nanoparticle [ 96 ] are used as nanocarriers.…”
Section: Cancer Therapeuticsmentioning
confidence: 99%
“…The tracking force of the ERMs causes retinal detachment [8]. At present there is no approved medicine for this eye disease [9]; the only treatment option with the surgery leads to the poor sight recovery [10,11]. Therefore, it is urgent to develop a pharmacological approach for the therapy of PVR.…”
Section: Introductionmentioning
confidence: 99%